Species of Cerambycinae (Insecta, Coleoptera, Cerambycidae) from east Paraná State (Brazil), with new geographic records - Barros, Rafael C.; Fonseca, Mailson G.; Jardim, Marcelo T.; Vendramini, Vinicius E.; Damiani, Bruno C.b.; Julio, Carlos E. A. (Zootaxa, 2020)
A list of species of Cerambycinae (Cerambycidae) collected in Iguaçu National Park (PNI) during the period from March 2012 to December 2018 is provided. A total of 135 species were sampled using different collection methods, all recorded for the first time in the PNI and including 21 new distribution records for the state of Paraná, and two new records for Brazil. The geographic distribution and material examined are stated for each species. A photograph of each newly recorded species is also provided.